Psychological factors crucial in the process of hematopoietic stem cell transplantation - Jakitowicz, Karolina; Piekarska, Agnieszka (Psychoonkologia, 2014)
From a psychological point of view, the process of hematopoietic stem cell transplantation is a complex process. In the literature, variables are analized during the stage before transplantation, during hospitalization and even several years after transplantation. Long-term treatment in isolation puts patients in a difficult emotional situation. Nowadays researchers include in their analysis factors such as the patients’ mental state, including: anxiety, depression, distress as well as social support and compliance. The aim of the study was to introduce the meaning of psychological factors in the process of hematopoietic stem cell transplantation based on a survey of contemporary literature.